Whorephobia: strippers on art, work, and life - Borden, Lizzie (Seven Stories Press, 2022)
"No one knows more than strippers about being looked at: as objects of desire, objects of curiosity, as angels or Jezebels or hookers with hearts of gold. In this anthology, twenty-three dancers whose careers span decades, geographies, and identities demand to be seen. Through stories from first nights on the job to the day they hung up their sky-high heels-or decided they never will-these writers offer glimpses into lives of camaraderie and celebration, joy, pride, despair, frustration, self-doubt, and fear. Their unfiltered perspectives on their lives, onstage and off, are a powerful counternarrative to the whorephobia that shrouds the conventional portrayals of strippers in crime movies, TV shows, music videos, newspaper articles, and legislative debates. Each of these illuminating essays and interviews peels away tired myths and salacious speculation and presents the naked truth: that sex work is real work and strippers are real people"--